2020
DOI: 10.1038/s41598-020-70508-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of legume-diet and sex of ducks on the growth performance, physicochemical traits of meat and fatty acid composition in fat

Abstract: Duck meat enjoys growing popularity among consumers. Alternative protein sources to soybean are being investigated to eliminate genetically modified components from the poultry’ diet. The aim of this study was to compare growth performance, quality of meat, and fatty acid composition in subcutaneous and abdominal fat from ducks fed a diet based on yellow lupin and rapeseed meal, sources of protein alternative to soybean meal (SBM). Ducks were allocated to different dietary treatment groups and reared for 8 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Data in Table (3) revealed that, no significant (P > 0.05) effect of genotype and sex on WHC of breast and leg muscles which ranged from 62.19 to 63.37 for breast meats and 65.74 to 66.49 for leg meats. The obtained results were in agreement comparatively with the results of Muhlisin et al, (2013) in imported commercial ducks recorded 65.90, but higher than in cherry valley English Pekin ducks were ranged between (58.01to 60.94) for breast muscles and (62.93 to 64.78) for leg muscles (Kowalska et al, 2020). In our study, breast and leg muscles exhibited higher pH24 values, in turn, it was exhibited higher WHC values.…”
Section: Physicochemical Propertiessupporting
confidence: 90%
See 1 more Smart Citation
“…Data in Table (3) revealed that, no significant (P > 0.05) effect of genotype and sex on WHC of breast and leg muscles which ranged from 62.19 to 63.37 for breast meats and 65.74 to 66.49 for leg meats. The obtained results were in agreement comparatively with the results of Muhlisin et al, (2013) in imported commercial ducks recorded 65.90, but higher than in cherry valley English Pekin ducks were ranged between (58.01to 60.94) for breast muscles and (62.93 to 64.78) for leg muscles (Kowalska et al, 2020). In our study, breast and leg muscles exhibited higher pH24 values, in turn, it was exhibited higher WHC values.…”
Section: Physicochemical Propertiessupporting
confidence: 90%
“…When compared to broiler chicken breast meats, duck breast muscles have a more favourable amino acid profile, with higher levels of leucine, lysine, tryptophan, phenylalanine, and tyrosine (Wołoszyn et al, 2006 andAli et al, 2007). Although much research has been conducted on the characteristics of domestic duck meats (Kim et al, 2010;Muhlisin et al, 2013;Qiao et al, 2017;Makram et al, 2017;Kokoszyński et al, 2019 andKowalska et al, 2020), data on carcass characteristics, nutritional value and physicochemical properties of game birds meat are very limited. Thus, this study aimed to evaluate carcass characteristics (body weight, carcass weight, dressing percentage and carcass composition), physicochemical properties (ultimate-pH, water holding capacity and color coordinates) as well as nutritional composition (basic chemical composition, content of some minerals, amino acids profile) of meat from two wild birds namely: pintail (Anas acuta) and shoveler (Spatula clypeata).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the lightness measurements of the non-uniformly fat leg muscles are often varied, in contrast to the results obtained for the breast muscles. Meat with too light a colour and uneven saturation is perceived as a raw material with low technological value, and especially a lower ability to retain its own water and higher culinary losses and hardness (Fletcher, 2002;Kowalska et al, 2020). It is also characterized by a poorer general appearance (Mancini and Hunt, 2005;Wołoszyn et al, 2009;Gornowicz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Most consumers consider colour to be a decisive factor in purchasing meat, identifying it with freshness (Troy and Kerry, 2010). The colour intensivity depends mainly on the physical structure of the muscle, and on the concentration and chemical form of the basic heme pigment, which is myoglobin, and is closely related to the content of intramuscular fat (Lacin et al, 2008;Kowalska et al, 2020). Depending on age and origin, the breast muscles of ducks contain from 63% to 84% red fibres and 16% to 37% white fibres, while in turkeys and chickens almost the entire breast muscle consists of white fibres (Mancini and Hunt, 2005;Wołoszyn et al, 2009).…”
mentioning
confidence: 99%
“…The most successful studies are considered to be the breeding of mulards obtained during the crossing of Peking ducks with Muscovy cock-ducks. In conditions of an extended fattening period and systematic breeding work to improve the quality indicators of duck meat while maintaining their productivity and viability, mulards can be considered an excellent raw material for the production of meat and culinary products with a reduced fat content [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%